The new institutional politics : performance and outcomes - Lane, Jan-Erik (Routledge, 2000)
The New Institutional Politics is a comparative study of the impact of political institutions upon outcomes, and covers some of the major themes in the new institutionalism. It looks at how various democratic institutions like Konkordanzdemokratie or corporatism promote better outcomes than Westminster institutions. The evaluation of the performance of political institutions covers the executive, the legislature and the judicial system. The book also looks at economic outcomes such as affluence and GDP growth as well as social ones like income distribution and quality of life. I.